Metabolomics study of human embryonic stem cell culture media - Alfaro Alfonzo, Antonio Alejandro (2015)
Self-renewal and pluripotency, the hallmarks of human embryonic stem cells (hESC), confer these cells with the capacity to expand indefinitely while maintaining the ability to differentiate into any cell type of the human body; thus, making hESC a valuable source of functional differentiated cells suitable for applications in regenerative medicine, drug discovery, biotechnology, biopharmaceuticals and developmental biology. However, the large-scale production of clinical-grade hESC, required for such applications, has been hampered by the current culture conditions in which hESC still depend on the use of mouse embryonic fibroblast-conditioned medium (MEF-CM) for their efficient growth. Therefore, investigation of the factors provided by MEFs is of the utmost importance to discover which components of MEF-CM allow the long-term expansion of undifferentiated hESC.